Visualization and analysis of mapping knowledge domains for coal pores studies. (15th July 2022) - Shao, Zhuangzhuang; Tan, Bo; Guo, Yan; Li, Tianze; Li, Xiaomeng; Fang, Xiyang; Wang, Feiran; Zhang, Qing; Wang, Haiyan
Highlights: Global research on coal porosity can be divided into three stages: In the embryonic stage (before 1998), the slow growth stage (1998–2007), and the rapid growth stage (2007–2020). China has advantages in terms of the number of published papers, cooperation and exchanges, the degree of attention, and the number of core authors in the field of coal porosity research. A complete set of research methods and processes of "Pore structure characteristics - Molecular simulation - Gas adsorption" will be formed. Abstract: The structure and quantity of coal pores determine the adsorption capacity of CO2, CH4, O2, N2 and other multi-element mixed gases, which is an important link connecting coal spontaneous combustion and gas disasters. To better grasp developments and trends in research on spontaneous combustion and gas disasters around the world and to promote theoretical research into their prevention and control, research progress on coal pores is reviewed and analyzed using bibliometrics based on a total of 5515 publications collected from the Web of Science Core Collection database. Yearly quantitative distribution of literature, country/region distribution, organization distribution, main source journal distribution, subject category distribution, research knowledge bases, research hotspots and frontiers are all analyzed, CiteSpace and Vosviewer are used to plot knowledge domain maps. The results show that the number of papers on spontaneous combustion studies has grown exponentially, that China, USA, Australia, France, Canada, Russia, Japan, Germany, and Poland are the most active countries in coal pores, but results from USA are the most influential, and that Fuel, E&F, IJCG, JNGSE, JLPPI and FPT are the main sources of published research on coal pores. At present, a framework for the basic theory and research methods is complete, but the research network is too centralized, and there are few frontier branches. Structure and quantity of coal pores research, Intrinsic mechanism of pore development, Influencing factors of pore development and microscopic chemical group evolution law are the main knowledge bases for coal pores studies. Research on coal pores has expanded from the macro level to the micro scale. Molecular simulation, pore structure characterization, methane reservoir and methane adsorption have become research frontiers.